7P MARKETING STRATEGY DESIGN IN AN EFFORT TO INCREASE SALES IN SPA SERVICES: A CASE STUDY AT FRESHMINT SPA LAMONGAN - Achmad, Marita Nur; Radianto, Wirawan Endro Dwi (Jurnal Bisnis dan Keuangan, 2026)
This study aims to design a 7P marketing strategy (Product, Price, Place, Promotion, People, Process, and Physical Evidence) to increase sales performance at Freshmint Spa Lamongan. The research is motivated by the growing competition in the local spa industry and the fluctuation in customer visits that affects business revenue. Using a qualitative approach with a constructivist paradigm and a case study method, data were collected through in-depth interviews, field observations, and documentation key informants including the owner, employees (therapists), and customers of Freshmint Spa. The data were analyzed through reduction, presentation, and inductive conclusion drawing. The results indicate that the integrated implementation of the 7P marketing mix can enhance competitiveness and strengthen positive customer perceptions of Freshmint Spa's services. The elements of promotion, people, and physical evidence have the most significant influence on increasing visit frequency and customer loyalty, while process and product play a crucial role in maintaining consistent service quality. The proposed strategy design is expected to serve as a guideline for Freshmint Spa in developing customer-oriented marketing efforts and as a practical reference for similar spa businesses to improve their sales performance sustainably.